Evaluation of Mukim Institutional Policies Using The CIPP Model In North Aceh Regency - Nanda Mahfudzah; Aiyub Aiyub; Muhammad Hasyem; Muklir Muklir; Muryali Muryali (Electronic Journal of Education, Social Economics and Technology, 2026)
This study aims to evaluate the policies of mukim institutions in North Aceh Regency using the CIPP Model (Context, Input, Process, and Product), identify supporting and inhibiting factors, and formulate recommendations to strengthen mukim institutions. The background of this research is based on the fact that the role of mukim in the local government system has not been optimal, even though it has a strong legal foundation. In its implementation, mukim faces various obstacles, such as unclear institutional position, budget limitations, low human resource capacity, minimal facilities and infrastructure, and weak coordination between institutions. This study uses a qualitative method with data collection techniques through interviews, observations, and documentation. The research informants include DPMG, sub-district heads, imum mukim, geuchik, tuha peut, mukim forum chairpersons, community leaders, and academics. The research results show that in terms of context, mukim is still socially relevant.  However, the clarity of the institutional position has not yet been established. In terms of input, resource support is still limited. In terms of process, policy implementation has not been effective, whereas in terms of product, the impact on residents is still limited within the government system. Recommendations are directed at strengthening authority, increasing resources, and optimizing institutional coordination.